Prospective comparison of conscious nasal versus oral video upper GI endoscopy in adults - Prabudoss, G. S.; Shah, Neha Prashant (International Surgery Journal, 2019)
Background: Endoscopy procedures are now becoming a mandate for any upper or lower abdominal conditions in addition to any radiological investigations. Patients have reluctance. It's mainly because of the painful experience they come across during upper GI endoscopy. If pain can be addressed during endoscope then all patients would smile after this procedure. The main objective of the study is to compare nasal endoscopy vs conventional endoscopy in gastrointestinal disorders. Methods: This prospective study was conducted in the department in the department of bariatric and metabolic surgery, Apollo Spectra Hospitals, Chennai. Totally 200 cases were included in the study for the study. Nasal packing was done with xylocaine and oxymetazoline without oral spraying of 10% xylocaine. Oral mouth gag was not inserted in nasal cases. Pain score was primarily used as a scoring method. Results: Comparative study was done for both groups for pain score, gag reflux, nausea, comfort level, voice change, image clarity, intervention procedures, and overall scoring was done. There was a significant advantage in the nasal endoscopy group. Conclusions: More screening endoscopies can be done for a large patient population to diagnose Gastro diseases at an early stage if a painless endoscopy can be offered instead of regular endoscopy hereafter. But however, the endoscopy suite should have regular scope for therapeutic procedures.